Consumer Trust Mediation: The Relationship Between Brand Image and Price Perception on Purchase Decisions at Mixue Nusaloka - Yusuf Hermawanto; Yunus Handoko; Ike Kusdyah Rachmawati (Green Publisher Indonesia, 2025)
The rapid growth of Indonesia's ice cream market, driven by changing consumer lifestyles and preferences, has intensified competition among brands. Mixue, a prominent Chinese ice cream and beverage chain, faces challenges in maintaining customer loyalty amidst rising competitors like AI Cha and Momoyo. Understanding how brand image and price perception influence purchase decisions, mediated by consumer trust, is critical for Mixue's strategic positioning. This study examines (1) the direct effects of brand image and price perception on trust and purchase decisions, and (2) the mediating role of trust in these relationships at Mixue Nusaloka BSD. A quantitative approach was employed, collecting data from 100 respondents via on-site questionnaires using a 5-point Likert scale. Partial Least Squares Structural Equation Modeling (PLS-SEM) analyzed the relationships between variables, with validity (loading factors ≥ 0.70, AVE ≥ 0.50) and reliability (Cronbach’s alpha ≥ 0.70) confirmed. Brand image and price perception significantly enhance trust (β = 0.430 and 0.488, respectively) and directly influence purchase decisions (β = 0.325 and 0.353). Trust also positively affects purchase decisions (β = 0.288) and mediates the price-perception-to-purchase link, not the brand-image-to-purchase relationship. Mixue should prioritize strengthening brand image and competitive pricing to foster trust and drive purchases. Future research should expand samples across locations, incorporate variables like service quality, and use mixed methods to enhance generalizability. These insights offer actionable strategies for F&B brands in competitive markets.